Integration of Information Competence in living libraries - Silva, Rafaela Carolina da [UNESP]; Vicentini Jorente, Maria Jose [UNESP]; Caldas, Rosangela Formentini [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2017)
The information is an input that supports social changes while enables the development in any field of human activity and the construction of knowledge. In this context, the ways of search, access and retrieve information launch multiple challenges to libraries and its professionals, where the use of traditional and digital Technologies constitutes a determining fator in creating hybrid information spaces. Hence, this study discusses, from an exploratory and literature research, such as hybrid library can become a place propels to learn and promoting information literacy. As a rescult, it is understood that the librarian can use the technology as a means of educating people in search, recovery, valuation, use and sharing of information processes. In conclusion, the living libraries and hybrid languages together with the information competence highlight the educational role of the librarie and have a direct commitment to the reduction of the so-called informational exclusion phenomenon.
Keywords: Citizenship; Hybrid languages; Information literacy; Social inclusion